Analysis of Accounting Education at the World’s Leading Universities and Its Comparison with Turkish Universities - Gül, Meltem; Aksu, İbrahim (My University, 2022)
The main purpose of the present research is to examine the undergraduate and graduate accounting\reducation courses given in the business administration programs at the top 100 universities in the world ranking\rpublished by Quacquarelli Symonds (QS) in terms of variables, including the course contents and course\rcategories, and compare the education at these universities with the accounting education at Turkish\runiversities. This comparison was made between the best universities in the world and the oldest universities, the\rbest universities, foundation universities, and newly established universities in Turkey. Ten universities were\rselected for each university group determined in Turkey.\rThe facts that the origins of the world’s best universities date back to very old times and that these\runiversities are located in developed countries and curricula are practice-oriented are among the remarkable\rresults of our study
Keywords: İşletme